Biomechanical Analysis of Table Tennis Racket Performance Using Makassar Ebony Veneer: A Comparative Study - Wachid Sugiharto; Nurhasan Nurhasan; Dwi Cahyo Kartiko; Muchamad Arif Al Ardha; Sauqi Sawa Bikalawan; Sheva Edhu Wigraha; Jay Mark Arbaan (CV. FOUNDAE, 2025)
Background: A racket's performance in controlling trajectory and manipulating the speed of the ball is greatly influenced by its structural characteristics and materials. The material of the table tennis racket can affect its performance, reducing the speed and control of the ball.Aims: The main objective of this research is to analyze the biomechanical performance of the Garuda Unesa Speed (GUS) table tennis racket made from Makassar ebony veneer as the main material and to compare its attributes, particularly speed and control, with those of high-end commercial rackets.Methods: This study applies a comparative design by comparing two types of rackets in table tennis. Two-dimensional kinematics analysis was also conducted using Kinovea software.Result: Based on the t-test results with a non-parametric path, all variables showed a significant difference with a p-value of 0.01 (Sig < 0.05). However, one variable did not show a significant difference, namely the velocity variable, with a p-value of 0.05 (Sig < 0.05). If examined from the average value, the speed variable has a slight difference (a difference of 0.5). The average speed data shows that the Makassar ebony wood veneer racket has better speed.Conclusion: Based on the results of biomechanical analysis, the reflection of the Makassar ebony wood veneer racket makes a good contribution to the speed and control of the table tennis racket. This finding has practical implications for designing an effective table tennis athlete smash and block game by utilizing the speed and control of a table tennis racket using Makassar ebony wood veneer.